2000
DOI: 10.1007/s001040051230
|View full text |Cite
|
Sign up to set email alerts
|

Operative Stabilisierung von per- und subtrochantären Oberschenkelfrakturen mit dem Gammanagel

Abstract: With the Gamma nail stable osteosynthesis of per- and subtrochanteric femur fractures is obtained independently of the fracture classification. Patients can be mobilized immediately. Technical errors must be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…Several studies have indicated median hospitalization periods of 12 to 37 days for Gamma nail implantation [ 19 - 21 ]. In our study, length-of-stay (LOS) ranged from 3 to 70 days for TGN and from 4 to 105 days for G3N.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated median hospitalization periods of 12 to 37 days for Gamma nail implantation [ 19 - 21 ]. In our study, length-of-stay (LOS) ranged from 3 to 70 days for TGN and from 4 to 105 days for G3N.…”
Section: Discussionmentioning
confidence: 99%
“…oder den Gleitnagel (53-56 min.) [1,3,5,8,17,22]. Dieser Umstand ist wahrscheinlich dadurch bedingt, dass in unserer Klinik die Anwendung beider Implantate aufgrund eines großen Patientenguts zum Routineeingriff geworden sind.…”
Section: Diskussionunclassified